THE ROLE OF ARTIFICIAL INTELLIGENCE IN HUMAN LIFE (Web of Teachers: Inderscience Research, 2026)
This article discusses the role of artificial intelligence in human life, its applications, and models developed across various fields. The advantages and disadvantages of artificial intelligence are highlighted. The paper analyzes key directions in the field of artificial intelligence and the opportunities its development has brought to humanity.